A Strategic Response to MOOCs: How One European University is Approaching the Challenge - Brown, Mark; Costello, Eamon; Donlon, Enda; Nic Giolla-Mhichil, Mairead (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
This paper briefly outlines some of the macro level claims, counter-claims and unresolved debates surrounding the rapid growth of Massive Open Online Courses (MOOCs) in Higher Education. It then reports insights, experiences and perceptions of those charged with developing a strategic institutional response to the challenges and opportunities presented by the MOOC movement framed within a wider European context. A description of the key drivers, strategic deliberations and major decision points at Dublin City University (DCU) is provided along with brief analysis of the advantages and disadvantages of a range of MOOC options set against an increasingly complex and rapidly evolving technology-enhanced learning terrain. In reflecting on this micro level experience, informed by lessons from the burgeoning literature on MOOCs, the paper aims to demonstrate the value of aligning key decisions with well-defined institutional drivers, which are used to help compare and contrast the affordances of different MOOC platforms. Finally, a number of strategic questions are presented that may help guide future decisions about the adoption of MOOCs by other institutions.